2021
DOI: 10.3390/jfb12010017
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Innovations in Osteochondral Regeneration: Insights from Biology and Inputs from Bioengineering toward the Optimization of Tissue Engineering Strategies

Abstract: Due to the extremely high incidence of lesions and diseases in aging population, it is critical to put all efforts into developing a successful implant for osteochondral tissue regeneration. Many of the patients undergoing surgery present osteochondral fissure extending until the subchondral bone (corresponding to a IV grade according to the conventional radiographic classification by Berndt and Harty). Therefore, strategies for functional tissue regeneration should also aim at healing the subchondral bone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 140 publications
0
21
0
Order By: Relevance
“…Connective tissues migrate rapidly and cover a defect area in osteochondral tissue to block an infection from external factors, and thin compact bones are formed following a pre‐generated fibrous layer. [ 67 ] However, this compact bone formed near the cartilage area often disturbs cartilage regeneration because the highly mineralized bony structure extinguishes chondrogenic cell migration and inhibits chondrocyte differentiation and chondral ossification. [ 67 ] Likewise, regenerated tissues in the Defect group showed CT and an adherent thin compact bone layer (CB) in the cartilage area (Figure 6e ), while the internal subchondral layer remained hollow with tissues rarely formed (Figure 6c,e ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Connective tissues migrate rapidly and cover a defect area in osteochondral tissue to block an infection from external factors, and thin compact bones are formed following a pre‐generated fibrous layer. [ 67 ] However, this compact bone formed near the cartilage area often disturbs cartilage regeneration because the highly mineralized bony structure extinguishes chondrogenic cell migration and inhibits chondrocyte differentiation and chondral ossification. [ 67 ] Likewise, regenerated tissues in the Defect group showed CT and an adherent thin compact bone layer (CB) in the cartilage area (Figure 6e ), while the internal subchondral layer remained hollow with tissues rarely formed (Figure 6c,e ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 67 ] However, this compact bone formed near the cartilage area often disturbs cartilage regeneration because the highly mineralized bony structure extinguishes chondrogenic cell migration and inhibits chondrocyte differentiation and chondral ossification. [ 67 ] Likewise, regenerated tissues in the Defect group showed CT and an adherent thin compact bone layer (CB) in the cartilage area (Figure 6e ), while the internal subchondral layer remained hollow with tissues rarely formed (Figure 6c,e ). In contrast, the structures were not found in the chamber‐implanted groups, which indicated that the chamber slowed the rapid infiltration of fibrous tissues in the cartilage area and secured a space for hard tissue regeneration (Figure 6e–h ).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the scaffold should support the defects mechanically until new bone is formed. Natural bone and cartilage are characterized by an anisotropic structure; thus, the scaffold should consist of a hierarchically organised architecture [ 4 , 5 ]. Another important point is that growth factors should be incorporated inside the structure to enhance osteogenesis, chondrogenesis and angiogenesis [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major problem of healthcare in the industrial community is the damage of joint cartilage, which is associated with the limited capacity of the tissue to regenerate [ 1 ]. The gold standard in cell therapy of cartilage diseases today is the method of autologous chondrocyte implantation which has some disadvantages [ 2 ].…”
Section: Introductionmentioning
confidence: 99%